Solutions for energy efficiency: 10 years of European Local Energy Assistance (ELENA) - European Investment Bank (EIB) (European Investment Bank (EIB), 2019)
The European Local Energy Assistance facility is run by the European Investment Bank on behalf of the European Commission. It helps the public and private sector implement energy efficiency, renewable energy and sustainable transport Investment projects, thus reducing greenhouse gas emissions. The ELENA facility promotes innovative solutions in energy efficiency and accelerates investments by building experience, facilitating financing and overcoming barriers.
Keywords: 330